2017
DOI: 10.1093/jhered/esx061
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Clines in Temperature and Salinity Tolerance in Tidepool Copepods

Abstract: Local adaptation has been understudied in marine systems, but might be expected to be pronounced in the tidepool copepod Tigriopus californicus, which has a broad geographic range and extremely restricted dispersal. Tolerance to temperature and salinity was assessed in 14 populations over a 20° latitudinal range. Adaptive differentiation to temperature and salinity was found at scales as low as 5.6 km. Latitudinal clines were significant, with northern populations being more tolerant of low salinity and less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 63 publications
9
34
0
Order By: Relevance
“…Our results complement work by Leong et al. () and allow us to make further inferences about intraspecific variation in salinity tolerance in T. californicus . Using an approach similar to our knock‐down exposures, Leong et al.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our results complement work by Leong et al. () and allow us to make further inferences about intraspecific variation in salinity tolerance in T. californicus . Using an approach similar to our knock‐down exposures, Leong et al.…”
Section: Discussionsupporting
confidence: 87%
“…In low salinity exposures, our treatments (0–5 psu) largely overlapped those of Leong et al. () (1–25 psu) and both our results and theirs show the northern populations are more tolerant to low salinity stress (Table ; Figure ). Previous work in Fundulus heteroclitus killifish (Brennan, Galvez, & Whitehead, ) and Eurytemora affinis copepods (Lee, Remfert, & Gelembiuk, ) showed that gains in low salinity tolerance came at the expense of high salinity tolerance.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations